Transformasi Sistem Publikasi Pendaftaran Tanah Melalui PTSL di Kantor Pertanahan Kota Medan - Maulida, Lisa; Imsar, Imsar (Abdimas Indonesian Journal, 2024)
Land is a two-dimensional part of the earth in the form of land, which in essence has a dual function for human life. Given the importance of land, the government needs to regulate it in the hope of providing welfare, happiness and certainty for the rights owners. With regard to rights, there needs to be evidence, namely a certificate issued by the Land Office. The mechanism for issuing certificates by referring to the negative land registration system has a tendency, but this system still causes conflict in the land sector. Starting from this conflict, the government carried out a complete systematic land registration program (PTSL), hoping to be able to provide certainty to the landowner community. The purpose of this study was to determine the complete systematic land registration (PTSL) at the Medan City Land Office as a form of change in the land registration publication system. This research method is a normative legal research with a conceptual approach, and regulations. The results of the study The negative land registration system with a positive tendency has not provided perfect legal certainty for land rights owners. Because land registration is not always certain to use the deed registration system (Registration of deeds) but also the registration of rights, uncertainty when there is a legal relationship between legal subjects in the land sector triggers disputes, conflicts and land problems even after following the procedures normalized in laws and regulations.